(untitled) (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2024)
The study examined data from 90 patients with comorbid disorders in primary headache. The patients underwent an objective clinical and neurological examination according to the standard scheme with an in-depth study of the neurological system. Patients are divided into 2 groups depending on gender